Utilizing renewable energy sources efficiently in hospitals using demand dispatch. (May 2020) - Vaziri, Shabnam Mahmoudzadeh; Rezaee, Babak; Monirian, Masoud Amel
Abstract: Health centers and hospitals can be categorized as one of the major consumers of electrical energy in building sectors. Due to their competitive environment, they need to decrease their costs, including energy costs. On the other hand, environmental problems, lack of fossil fuels, and high energy consumption lead to using alternative energy generation methods like renewable energy sources (RESs). In this paper, we consider that the hospital can produce part of its energy from RESs for cost reduction and we implement demand dispatch energy program for using RESs efficiently. The challenge is that the main goal of hospital is providing health services not energy cost reduction. Therefore, we present a bi-objective formulation for using RESs in hospitals in a way to minimize costs and dissatisfaction by scheduling the activities of the hospital by considering hospital's specific constraints and limitations. With the help of the proposed model, hospitals will decrease energy costs while maintaining comfort of patients and surgeons at the same time. The model is solved using real data of a hospital in Iran, and sensitivity analysis on different parameters is done. The proposed model will cause reduction in energy cost of the hospital by implementing demand dispatch program for using RESs in the hospital. Highlights: Health centers are considered as a new type of energy consumers. Wind turbines and solar panels are used for energy generation in hospitals. Activities are scheduled in a way to minimize the cost and the dissatisfaction of patients and surgeons. The limitations of hospitals are considered in the mathematical model. The proposed model reduces energy use in peak hours and shifts the loads to time periods with renewable energy generation.